2003
DOI: 10.1111/j.1521-0391.2003.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Desipramine or Carbamazepine to Placebo for Crack Cocaine‐Dependent Patients

Abstract: The authors compared the effects of desipramine or carbamazepine to placebo in an intensive outpatient program for cocaine abuse. Subjects recruited from an urban drug treatment program were randomly assigned to a double-blind, placebo-controlled, eight-week trial of desipramine, carbamazepine, or placebo. Patient ratings, urine drug screens, and blood samples were obtained weekly. Using survival analysis, the three groups did not differ in time to drop out of treatment. While subjects improved over time on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In addition, it would have been useful to have directly compared atomoxetine with desipramine because the latter drug has been examined extensively as a pharmacotherapy for cocaine dependence. The results of clinical trials in which the therapeutic efficacy of desipramine has been evaluated have been mixed (reviewed in Lile & Nader, 2003), although a meta-analysis of six of these trials indicated that desipramine was significantly more effective at promoting abstinence compared with placebo (Levin & Lehman, 1991), and research with this drug has continued (e.g., Campbell et al, 2003; Kosten et al, 2003). Despite the benefits of this additional control condition, including yet another drug in the test phase would have further increased an already lengthy experimental protocol, which might have increased subject attrition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it would have been useful to have directly compared atomoxetine with desipramine because the latter drug has been examined extensively as a pharmacotherapy for cocaine dependence. The results of clinical trials in which the therapeutic efficacy of desipramine has been evaluated have been mixed (reviewed in Lile & Nader, 2003), although a meta-analysis of six of these trials indicated that desipramine was significantly more effective at promoting abstinence compared with placebo (Levin & Lehman, 1991), and research with this drug has continued (e.g., Campbell et al, 2003; Kosten et al, 2003). Despite the benefits of this additional control condition, including yet another drug in the test phase would have further increased an already lengthy experimental protocol, which might have increased subject attrition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, desipramine resulted in a 40% decrease in ratings of cocaine craving, yet had no effect on the amount of cocaine self‐administered in the human laboratory (Fischman et al . 1990) or used in the clinic (Campbell et al . 2003).…”
Section: Methodsmentioning
confidence: 99%
“…No study among the six trials involving selective serotonin reuptake inhibitors (fluoxetine, paroxetine, fenfluramine) found evidence of anti-craving effects [ 21 , 25 , 27 , 28 , 33 , 36 ]). Among the trials involving dual action in 5HT and NA signaling (venlafaxine, citicoline, nefazodone, desipramine) [ 20 , 23 , 24 , 26 , 29 , 30 , 31 , 34 ], two found a statistically significant reduction in cocaine craving: one study administering long-term desipramine [ 26 ], and one study administering long-term nefazodone [ 24 ]. Mirtazapine 30 mg daily showed significant anti-craving effect in one study [ 32 ], while no effect in craving in another trial [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [ 80 ] of two [ 23 , 80 ] comparing carbamazepine to placebo showed a significant decrease in craving. The anticonvulsant topiramate was found to have anti-craving effects in two [ 81 , 82 ] out of four trials [ 81 , 82 , 83 , 86 ].…”
Section: Resultsmentioning
confidence: 99%